(untitled) (SCIENCE TIME JOURNAL, 2024)
This article provides an overview of methodological approaches in contemporary pedagogical research. It highlights various research methods and techniques used to investigate educational phenomena, improve teaching practices, and enhance student learning outcomes. The article discusses quantitative research, qualitative research, mixed methods research, action research, case study research, design-based research, ethnographic research, longitudinal research, historical research, systematic review and meta-analysis, participatory research, experimental design, design-based implementation research, network analysis, neuroscientific research, virtual and augmented reality research, comparative education research, and discourse analysis. Each approach is briefly described, emphasizing its unique characteristics, applications, and contributions to the field of pedagogy. The article aims to assist researchers, educators, and policymakers in understanding the diverse methodological options available for conducting rigorous and insightful pedagogical research.